Corporate entrepreneurship capabilities management and development in the context of organizational rejuvenation - Piehl, Elsi Tuulia (My University, 2022)
The fast-pace and continuously evolving business environment of today sets new challenges for business actors in the markets, as firms must engage in continuous innovation and rejuvenation to remain relevant and ahead of the competition. Corporate entrepreneurship (CE), entrepreneurship within existing organizations, is a crucial part of achieving this renewal. The organizational rejuvenation dimension is especially relevant from this perspective, as it covers the corporate entrepreneurship agenda targeted toward renewing the organization itself. Yet, the methods and activities through which this organizational rejuvenation and the related capabilities are managed and developed are not distinguished in existing literature. Therefore, this thesis aims to fill this gap. The research objective of this thesis is to explore how corporate entrepreneurship capabilities targeting organizational rejuvenation are managed and developed. Thus, the theoretical frame- work of the study constitutes of literature streams related to corporate entrepreneurship, dy- namic capabilities, and the management research surrounding the topics. The study applies a qualitative research method, using a single-case study to explore the research phenomenon. The empirical data for the study is gathered through eight semi-structured interviews. The se- lected interviewees represented various functions of the organization and hosted diverse back- grounds and previous experience. The results suggest five capabilities are particularly important for achieving organizational reju- venation: organizational change, innovation, learning, leadership, and culture. The capabilities’ interplay additionally impacts the organization’s ability to rejuvenate and manage or develop these capabilities. The results further indicate that management level activities are vital for fos- tering an environment that enables corporate entrepreneurship to occur, aiding with resource allocation, facilitating trust, and allowing individuals practice entrepreneurship and showcase their innovativeness. It is further concluded that despite the significance of management sup- port, the entrepreneurial individuals within the firm are the most important facilitators of cor- porate entrepreneurship, and thus HRM practices such as hiring, and rewards are important for achieving organizational rejuvenation. The thesis further presents key aspects that impact capa- bility development and management for each of the specific capabilities described above.
Keywords: entrepreneurship; organisations (systems); intrapreneurship; capability; dynamic capabilities; fi=Johtaminen ja organisaatiot|en=Management and Organization|; Master’s Programme in Strategic Business Development